Departure - Umea University graduation exhibition 2000 - Gavlak, Sarah E.; Hannula, Mika; Krüger, Anders; Vallance, Jeffrey; BildMuseet, Umea; Wetterling Gallery, Stockholm (Umea : Umea University - Umea Bildmuseet, 2000)
Aglert, Oskar ; Andrée, Mia ; Frid, Ase ; Gustavsson, Patrik ; Häyhtiö, Sofia ; Jensen, Tatiana ; Johansson, Magdalena ; Lantto, Markus ; Larsson, Christoffer ; Roussinova, Peter Persson : Lora ; Sundin, Ronnie ; Tomasson, Emil
Speciale kast, CD (zelfde code)
biografie
Departure - Umea University graduation exhibition 2000, BildMuseet, Umea, 06.05 - 21.05.2000 ; Wetterling Gallery, Stockholm, 24.05 - 31.05.2000
Engels
kunstcatalogus